Shaping a corporate culture : dissonances between the narratives of owners and employees in a company - GAPPY, JOHN MARTIN BERNARD (Archīum Ateneo, 2017)
Ortners practice theory is concerned with the dominant constraints of culture and subversive tothe idea of culture as being simply reproduced. The purpose of this research is to explore the waythat culture is created, reinforced, contested, and transformed within the context of a Filipinosmall enterprise. An ethnographic approach was conducted to grasp the enactments of culture atSee & Install through the prism of job appointments. Findings revealed that company ownersapply certain aspects of Filipino family practices as guide for workplace behaviors. On one hand,the family metaphor perceives employees more as attendants rather than co-workers, expectingthem to comply to employers demands, and does not give due importance to workers agency.On the other hand, employees exercise agency in a variety of ways that continuously challengethe owners preferred cultural system. A more culturally attuned leadership style is thussuggested so that a dynamic interplay between company structure and employees agency enactmore positive workplace practices and experiences.